Clinicians' guide to adult ADHD assessment and intervention - Goldstein, Sam 1952- (Academic Press, 2002)
This text offers practicing clinicians strategies, interventions, suggestions, guidance and ideas to work with adults struggling with Attention Deficit Hyperactivity Disorder, and is intended as a reference to which clinicians will turn time and time again as issues or problems present themselves. The text will also provide a comprehensive review of the scientific literature and expand the development of an ongoing model to treat Attention Deficit Hyperactivity Disorder
Includes bibliographical references and index
Keywords: Hyperactivité chez l'adulte; PSYCHOLOGY / Mental Illness; Attention-deficit disorder in adults; Attention Deficit Disorder with Hyperactivity / diagnosis; Adult; Attention Deficit Disorder with Hyperactivity / therapy